The Difference of Iron Level Based on the Cooking Time and Methods Applied on the Tempeh and Beef Liver: An Experimental Study - Prasetyo, Aghnaita Firda; Farapti, Farapti; Isaura, Emyr Reisha (Universitas Airlangga, 2022)
Iron deficiency is a common cause of anemia, so it is necessary to consume adequate food sources of iron to prevent anemia. One way that can be used to fulfill iron intake is by minimize the loss of iron in the cooking process. Beef liver and tempeh are the common iron food sources in Indonesia. This study aimed to analyze the effect of cooking methods and cooking times on the iron levels of beef liver and tempeh. This study was an experimental. There are three cooking methods used in this study: boiling, boiling + stirring, and steaming, and two cooking times were applied for each treatment: 10 and 15 minutes. We were measured the iron level using the Atomic Absorption Spectroscopy (AAS) method. The study results showed that boiling decreased the iron content of tempeh and beef liver by a range of 22.43-34.61%, boiling+stirring decreased the iron content by a range of 42.24-49.64%, and steaming decreased the iron content by a range of 11.93-19.09%. Based on cooking time, cooking for 15 minutes showed a higher reduction in iron content than cooking for 10 minutes. However, cooking methods and cooking times significantly affect the iron level of beef liver and tempeh while steaming for 10 minutes has the highest iron level.